In Favour of Experiential Learning: An Endeavour Alluding to Students’ Cognitive Milieu - Rizki Febri Andika Hudori (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: This retrospective article portrays the endeavor associating the learning of language and of subject matter under the philosophy of experiential learning. Specifically, it seeks to point out how the adopted framework aids English instructors to embolden and sustainably propel junior high school students cognitively to learn English. The cognition manifests itself as a crux which in this case is perceived as the uttermost issue. It is due to the psychological characteristics of the students, which is mainly pertinent to their limitation to deal with the abstract, that numerous favourable strategies attending to experiential learning are seen to be mostly doable and helpful. Relying on the pedagogical premise, the English instructors are enabled to bestow powerful impetus arousing students’ motivation through fostering their exuberant involvement in the classroom orchestra.Key words: experiential learning, cognition, and involvement